2002
DOI: 10.1590/s1516-89132002000500020
|View full text |Cite
|
Sign up to set email alerts
|

Drug interaction with radiopharmaceuticals: effect on the labeling of red blood cells with technetium-99m and on the bioavailability of radiopharmaceuticals

Abstract: The evidence that natural and synthetic drugs can affect radiolabeling or bioavailability of radiopharmaceuticals in setting of nuclear medicine clinic is already known. However, this drug interaction with radiopharmaceuticals (DIR) is not completely understood. Several authors have described the effect of drugs on the labeling of blood elements with technetium-99m (99mTc) and on the biodistribution of radiopharmaceuticals. When the DIR is known, if desirable or undesirable, the natural consequence is a correc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
25
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 22 publications
0
25
0
Order By: Relevance
“…Thus, it is important to develop models that can describe the possible in vitro and in vivo drug interactions. Some authors have described that synthetic or natural products, can alter the labeling of blood constituents with Tc-99m (Braga et al, 2000;Gomes et al, 2002;Bernardo-Filho et al, 2005;Neves et al, 2007). Moreno et al, (2004), have evaluated the effect of a Ginkgo biloba extract on labeling of blood constituents with Tc-99m using in vitro and in vivo study: a reduction of radiolabeling of blood cells was observed with the in vitro method (Moreno et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it is important to develop models that can describe the possible in vitro and in vivo drug interactions. Some authors have described that synthetic or natural products, can alter the labeling of blood constituents with Tc-99m (Braga et al, 2000;Gomes et al, 2002;Bernardo-Filho et al, 2005;Neves et al, 2007). Moreno et al, (2004), have evaluated the effect of a Ginkgo biloba extract on labeling of blood constituents with Tc-99m using in vitro and in vivo study: a reduction of radiolabeling of blood cells was observed with the in vitro method (Moreno et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Radiopharmaceuticals (radiobiocomplexes) (6) are radioactive tracers employed in nuclear medicine for the study of several morphological and physiological conditions, such as blood flow and absorption, biodistribution, and metabolism in target and nontarget organs (7).…”
mentioning
confidence: 99%
“…Many natural and synthetic products have been reported to affect the biodistribution of different radiobiocomplexes (6)(7)(8)(9). The incorporation of a radionuclide into a drug formulation permits the determination of the biodistribution kinetics and the release sites of the latter (10,11).…”
mentioning
confidence: 99%
See 2 more Smart Citations